Automated body condition scoring of dairy cattle : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Manawatū, New Zealand - O'Connor, Aaron (Massey University, 2018)
This research demonstrates the development and implementation of an automatic body condition scoring system for dairy cattle that can operate in a real-world environment. Body condition scoring is a subjective method used for measuring changes in energy reserves in many animals, including dairy cattle. These energy reserves can be measured by analysing specific regions on the cow to estimate the amount of fat the animal is carrying. This information allows for greater management of the herd by adjusting the feeding strategies to ensure that each cow is at an optimal condition score. Maintaining an optimal condition throughout the year has implications for milk yield, reproductive performance, animal welfare, and overall farm profits. Current condition scoring methods are manual and are highly subjective, time consuming, expensive, and require a high level of training and competency. These limitations have created a demand for an accurate and objective scoring system. This research presents an automated system that utilises a single camera to be placed above the path of the cow at the entrance or exit to a milking platform or weigh scale. When the cow passes in view of the camera, the features are automatically extracted and converted to a conditions score. Tests have shown that the system successfully predicted the condition score within half a point of the true score for 83% of the 710 cows scored, and 96% within one point.
Keywords: Dairy cattle; Condition scoring; Automation; Imaging systems; Design and construction; 409901 Agricultural engineering